PENERAPAN MODEL PEMBELAJARAN DISCOVERY PADA MATERI GAYA MAGNET UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Nurjanah, Hanifah Ismi; Jayadinata, Asep Kurnia; Julia, Julia (Jurnal Pena Ilmiah, 2017)
Research in class V SDN Sukahati background on the lack of understanding of students on the material, and the implementation of less learning to arouse students' interest to learn. Efforts to fix the problem by applying the Discovery learning model. The problem is corrected through Classroom Action Research (PTK) with research design model Kemmis and Taggart. Instruments used include teacher performance observation sheets, student activities, student learning outcomes, interview guides, and field notes. This study was completed in three cycles. The data obtained in the planning cycle 84%, 92.2% cycle II, and 100% cycle III. At the implementation of 83% cycle I, 90.5% cycle II, and 100% cycle III. Furthermore student activity in cycle I 62,14%, cycle II 86,9%, and at cycle III 90,2%. Then the result of study from 34 students, on cycle I as many as 17 students (50%) complete, cycle II 28 students (82,4%), and cycle III 31 student (91,2%). Thus, the Discovery learning model can improve student learning outcomes